The Effect of Multimedia-Based Education on the Management of Hypertension on Behavioral Change for Stroke Prevention - Suratun; Nelly Yardes; Ni Luh Putu Ekarini; Tri Prasetyorini; Endang Banon; Dewi Lusiani (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This study aims to determine the effect of multimedia-based education on the management of hypertension on changes in stroke prevention behavior. The method in this study uses a quasi-experimental pre-post and post-test with control group design. The study population was all elderly with hypertension in Cipayung District, East Jakarta. The sampling technique uses purposive sampling. The number of samples in 64 respondents, in the intervention group and the control group. The method of data collection by pre-post and post-test, the data characteristics of respondents, knowledge, attitudes and actions using a questionnaire. While the blood pressure data checks the respondent. The study was conducted in the working area of ​​the Cipayung District Health Center in East Jakarta, the time of the study was from April to November 2019. Interventions that were conducted to respondents were multimedia-based education using Video and Modules. Univariate and bivariate data analysis, using the dependent and independent t-test while multivariate data analysis using the mancova test. The results showed that the average age of respondents was 63 years in the intervention group, while the control group was 62 years. The majority of respondents are female, not working and have low education both in the control and intervention groups. There are significant differences in multimedia-based education on respondents' knowledge, attitudes, actions and blood pressure. There is a significant influence between respondent's age, occupation and systolic blood pressure on stoke prevention behavior. Conclusion: There is a significant difference in multimedia-based education on changing the behavior of respondents for stroke prevention.